A Real-Valued Kalman Estimation Method for Harmonic Signal Analysis in Biomedical Applications - Rodríguez-Maldonado, Johnny; Platas-Garza, Miguel Ángel; Zambrano-Serrano, Ernesto (Revista Mexicana de Ingenieria Biomedica, 2024)
This work presents a methodology for obtaining the harmonic estimation of biomedical signals such as electrocardiogram, cardiorespiratory and blood pressure signals. The proposed methodology is achieved using polynomial approximation and the Kalman filter. As advantage, the technique includes instant estimations of signal harmonics and its derivatives using a real-valued model. Furthermore, a comparison of the results is conducted with the Savitzky-Gola, nonlinear tracking differentiator methods, extended state observer and digital differentiator base on Taylor series. The results suggest that the proposed method has the potential to enhance the quality of signal measurements, especially in the presence of noise.